2006
DOI: 10.1242/jeb.02121
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and blood gas dependence on digestive state in the Savannah monitor lizardVaranus exanthematicus: an assessment of the alkaline tide

Abstract: SUMMARY A large alkaline tide (up to 20 mmol l–1 increase in bicarbonate concentration [HCO3–] with an accompanied increase in blood pH) has previously been reported for some carnivorous reptiles within 24 h after ingesting a large meal. This phenomenon has been attributed to the secretion of large amounts of H+ ions into the stomach, which is required for digestion of large prey items. To test the generality of this phenomenon in carnivorous reptiles, this study quantified the metabolic and aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Loss of diaphragmatic function disabled the hepatic piston pump, thus aspiration could only be achieved via alterations in intercostal or abdominal muscle activities. The resting breathing patterns of crocodiles in this study at both 20°C and 30°C, and in response to hypercapnia, were similar, both before and after surgery, to those previously measured in juvenile alligators and crocodiles under similar conditions (Farmer and Carrier, 2000c;Hartzler et al, 2006a;Munns et al, 1998;Munns et al, 2005). This suggests that the surgical intervention did not adversely alter the animals' breathing patterns, and the consistency of ventilatory and metabolic data both before and after surgery precluded the need for shamoperated controls.…”
Section: Discussionsupporting
confidence: 80%
“…Loss of diaphragmatic function disabled the hepatic piston pump, thus aspiration could only be achieved via alterations in intercostal or abdominal muscle activities. The resting breathing patterns of crocodiles in this study at both 20°C and 30°C, and in response to hypercapnia, were similar, both before and after surgery, to those previously measured in juvenile alligators and crocodiles under similar conditions (Farmer and Carrier, 2000c;Hartzler et al, 2006a;Munns et al, 1998;Munns et al, 2005). This suggests that the surgical intervention did not adversely alter the animals' breathing patterns, and the consistency of ventilatory and metabolic data both before and after surgery precluded the need for shamoperated controls.…”
Section: Discussionsupporting
confidence: 80%
“…However, body temperature as well as the size, composition and frequency of meals can alter the metabolic response to feeding in reptiles (Beaupre, 2005;Bennett and Hicks, 2001;Hartzler et al, 2006;Hicks et al, 2000;Secor et al, 2000;Toledo et al, 2003;Wang et al, 2012). Pilot data from lizards in the present study, voluntarily fed their captive (relatively low protein) diet at 30°C, demonstrated that the duration of metabolic rate elevation caused by feeding is ~48h.…”
Section: Experimental Protocolmentioning
confidence: 50%
“…2A). A number of studies have shown that plasma Cl -levels drop following a meal in some ectotherms (Busk et al, 2000a;Hartzler et al, 2006), whereas it remains stable in others (Overgaard et al, 1999;Busk et al, 2000b). Studies have also shown that HCO 3 -/Cl -exchange is 1:1 (for a review, see Grosell, 2006), which would not explain why there is such a substantial difference between the large drop in plasma Cl -(17 mmol l -1 ) and the moderate rise in plasma HCO 3 -(4 mmol l -1 ) in catheter-fed fish after 6 h ( Fig.…”
Section: Role Of the Gills And Kidney In Recovery From The Alkaline Tidementioning
confidence: 99%
“…There are now many examples in the literature of post-prandial alkaline tides occurring in reptiles and mammals (Regev et al, 2001;Ozaki et al, 2000;Arvedsen et al, 2005;Hartzler et al, 2006;Weber and White, 1986). Comparative information of a post-prandial alkaline tide in fish (i.e.…”
Section: Introductionmentioning
confidence: 99%